Sistem Pakar Diagnosis Gangguan Jiwa Dengan Metode Case Base Reasoning (CBR) Dan Similarity Probabilistic Symmetric - Zuhri, M; Yupianti, Yupianti; Fredricka, Jhoanne (UNIVED Press, 2026)
This study develops an expert system for diagnosing mental disorders using the Case Based Reasoning (CBR) method and the Symmetric Similarity Method to detect types of psychiatric disorders based on patient symptoms. The CBR method is used to reason about new cases by comparing them to past cases stored in the knowledge base, while the Symmetric Similarity Method is used to calculate the degree of similarity between those cases. The research was conducted at Soeprapto Psychiatric Hospital (RSJ Soeprapto) in Bengkulu and developed the diagnostic expert system using Laravel and MySQL. With this system, the diagnostic process can be carried out more quickly and efficiently, and it can be used by the public for early detection before receiving a direct examination from a psychiatric specialist.